Continued glacial retreat linked to changing macronutrient supply along the West Antarctic Peninsula - Rhiannon L. Jones; Michael P. Meredith; Maeve C. Lohan; E. Malcolm S. Woodward; Katrien Van Landeghem; Kate Retallick; Oliver Flanagan; Mehul Vora; Amber L. Annett (Marine Chemistry, 2023)

Blue carbon gains from glacial retreat along Antarctic fjords: What should we expect? - David K. A. Barnes; Chester J. Sands; Alison Cook; Floyd Howard; Alejandro Roman Gonzalez; Carlos Muñoz–Ramirez; Kate Retallick; James Scourse; Katrien Van Landeghem; Nadescha Zwerschke (Global Change Biology, 2020)
Rising atmospheric CO 2 is intensifying climate change but it is also driving global and particularly polar greening. However, most blue carbon sinks (that held by marine organisms) are shrinking, which is important as these are hotspots of genuine carbon sequestration. Polar blue carbon increases with losses of marine ice over high latitude continental shelf areas. Marine ice (sea ice, ice shelf and glacier retreat) losses generate a valuable negative feedback on climate change. Blue carbon change with sea ice and ice shelf losses has been estimated, but not how blue carbon responds to glacier retreat along fjords. We derive a testable estimate of glacier retreat driven blue carbon gains by investigating three fjords in the West Antarctic Peninsula (WAP). We started by multiplying ~40 year mean glacier retreat rates by the number of retreating WAP fjords and their time of exposure. We multiplied this area by regional zoobenthic carbon means from existing datasets to suggest that WAP fjords generate 3,130 tonnes of new zoobenthic carbon per year (t zC/year) and sequester >780 t zC/year. We tested this by capture and analysis of 204 high resolution seabed images along emerging WAP fjords. Biota within these images were identified to density per 13 functional groups. Mean stored carbon per individual was assigned from literature values to give a stored zoobenthic Carbon per area, which was multiplied up by area of fjord exposed over time, which increased the estimate to 4,536 t zC/year. The purpose of this study was to establish a testable estimate of blue carbon change caused by glacier retreat along Antarctic fjords and thus to establish its relative importance compared to polar and other carbon sinks.